Effect of Understanding of Tax Regulations and Quality of Tax Services on Taxpayer Compliance (Study on Ternate KPP) - Astry Muningsih (CV. Proaksara Global Transeduka, 2025)
Income Tax Article 25 refers to the payment of income tax in installments, with the aim of easing the financial burden on taxpayers, considering that the tax payable must be settled within one fiscal year. This paper serves as a foundation for understanding tax regulations applicable to taxpayers, particularly in relation to compliance with Corporate Income Tax (PPh Article 25). The research was conducted at the Ternate KPP Pratama. This study uses primary data obtained from individual or corporate taxpayers engaged in business activities subject to PPh Article 25, which requires monthly installment payments of income tax during the current tax year. The test results show that understanding of tax regulations has a positive and significant effect on taxpayer compliance. The greater the taxpayer’s understanding of applicable tax regulations, the higher their level of compliance in fulfilling tax obligations. The research findings indicate that a strong grasp of tax regulations can significantly enhance taxpayer compliance. Conversely, limited understanding may hinder the effective enforcement of compliance. Therefore, the higher the level of understanding taxpayers have of the applicable tax regulations, the less likely they are to violate them, thereby promoting greater compliance. Additionally, the quality of taxation services also has a positive and significant impact on taxpayer compliance. The better the quality of these services, the more likely taxpayers are to comply with their obligations. Improved tax service quality leads to increased trust and satisfaction among taxpayers, ultimately encouraging better compliance with tax regulations.